Tracing the geographical origin of Spanish mango (Mangifera indica L.) using stable isotopes ratios and multi-element profiles. (July 2021) - Muñoz-Redondo, J.M.; Bertoldi, D.; Tonon, A.; Ziller, L.; Camin, F.; Moreno-Rojas, J.M.
Abstract: The stable isotopes of five bio-elements (δ 13 C, δ 15 N, δ 34 S, δ 2 H, δ 18 O) and the elemental composition profile combined with chemometrics were used to differentiate the geographical origin of commercial samples of mango, aimed at contributing to the existence of a Spanish protected geographical indication (PGI). Eighty commercial mangoes from all over the world (Spain, Mexico, Peru, Brazil, Ivory Coast, Equatorial Guinea and Senegal), collected during two consecutive harvests, were analysed and assessed by means of univariate and multivariate data analyses, establishing the main variation sources linked to the origin of the mangoes. The data obtained from each analytical platform were assessed separately and in combination, resulting in three models whose discriminatory power (Spanish vs others) was compared. The model fitted for the stable isotope approach yielded a sensitivity of 100%, meaning that the Spanish mangoes were correctly classified in all the cases, against the 97.6% for multi-element analysis. The combined use of stable isotopes and elemental composition led to the most accurate geographical discrimination of Spanish mangoes, making it possible to select three stable isotope ratios (δ 15 N, δ 18 O, δ 34 S) and six elements (Cd, Se, Cs, As, Pb and Ba) as the main indicators of the geographic origin of mango. The results of this study revealed the feasibility of tracing the provenance of mango through either of the two analytical strategies or by combining them to obtain a more accurate classification. Highlights: The main stable isotope ratios tracing the origin of Spanish mangoes were identified. The main elements tracing the origin of Spanish mangoes were identified. Results were evaluated by means of PLS-DA models. Combination of stable isotope ratios and element profile improved model performance. Results contribute towards the existence of a potential Spanish PGI of mango.